Analysing EU Sectoral Trade Integration with Gravity Model of Trade - Ildiko Virag-Neumann (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
The objective of this research is provide an overview of EU integration effects on international trade and sectoral trade integration as reported by a relevant gravity model and fixed effect panel estimation. In order to evaluate the EU economic integration effects across sectors, I build up a sectoral gravity model. Gravity model based studies have achieved empirical success in explaining various types of flows, including migration, commuting, goods, money capital information and international trade. Trade within Europe is still impeded by significant barriers. In particular, there remain many non-tariff barriers, including so-called TBT "Technical Barriers to Trade”. (Theie, 2014) These barriers result from regulations by requiring specific product characteristics or production processes. (Chen and Novy 2011) The sectoral trade integration analysis is deepened with capturing TBT coefficient compiled for separate sectors. The aim of this paper is to explore the implicit trade obstacles or barriers that still exist among EU members and to prove the trade-reducing effect of such remaining obstacles in separate sectors. My hypothesis is that different types of goods might face diverse entry barriers, and thus their gravity equation coefficients would differ across sectors.
Keywords: F15; O52; 330; EU economic integration; gravity model of trade; panel estimation; economy; market